Effect of prohexadione-calcium application and irrigation technique on plant growth, physiological changes and postharvest quality of roselle (Hibiscus sabdariffa L.) - Ahmad Azmi, Mohamad Nazrin (2021)
Hibiscus sabdariffa (roselle) belongs to the Malvaceae family and is commonly used to make healthful beverages and medicine. Roselle calyces are high in functional properties such as vitamin C, anthocyanin, and other phenolic compounds. They are beneficial to health since they are a powerful source of antioxidants as well as a natural food colourant. However, factors such as species, agronomic practices and environmental conditions are greatly influencing the contents of vitamin C and anthocyanin pigments in H. sabdariffa. Moreover, changes in temperature conditions during harvest and postharvest caused a greater loss of both vitamin C and anthocyanin, which eventually resulting in poor color and quality of calyces. In addition, the application of prohexadione-calcium (Proca) and partial rootzone drying (PRD) are reported can influence and regulate the content of vitamin C and anthocyanin pigment. Thus, a study was conducted to determine the effect of Proca application and PRD on growth, physiological changes and postharvest quality attributes of roselle. In 1st experiment, two different varieties of roselle (UMKL-1 and UKMR-2) were planted in a greenhouse and sprayed with four different concentrations of Proca (0, 100, 200 and 300 mg L-1) at 45 days after transplant (DAT). Roselle calyx was harvested at 75 DAT and analysed. Plant height of roselle showed a reduction in growth with all Proca application with 300 mg L-1 gave the highest shoot reduction among other concentrations. Whereas calyx postharvest quality attributes showed that Proca application increased pH, C* value and anthocyanin content. However, the Proca treatment, had minimal significant interaction with the generation of vitamin C or generally known as ascorbic acid (AA) which was found in the highest concentration in the UMKL-1 line. As for roselle variety, UMKL-1 scientifically showed greater performance with Proca application on calyx postharvest quality attributes as compared to UKMR-2. As for the 2nd experiment, study was focused on Proca different frequency (0 = without spray, Once = 45 DAT, Twice = 45 and 52 DAT and Thrice = 45, 52 and 59 DAT) on selected variety of roselle (UMKL-1), sprayed with selected Proca concentration (100 mg L-1) from 1st study. Then, the PRD irrigation technique begins on the roselle plant after 30 DAT to compare full irrigation and PRD irrigation. The color attributes (L*, C*, h° value), physical (firmness, fresh weight of leaves, stem, total yield) and biochemical content [total anthocyanin content, ascorbic acid (AA) content, titratable acidity (TA), soluble solid concentrations (SSC)] were determined. The results demonstrated that 100 mg L-1 of Proca treatment accelerated AA and anthocyanin content. While calyx sprayed at 1x and 2x frequency increased anthocyanin content, Proca sprayed at 3x frequency increased the amounts of AA without affecting other postharvest quality parameters. These findings suggest that the application of the Proca and PRD technique presented in this study should be adopted for commercial production in the future.